Towards a Market Economy : Structures of Governance - Dhonte, Pierre (IMF Working Papers; Working Paper ;, 1997)
This paper proposes an operational interpretation of the concept of economic governance. It argues that the capacity of governments to credibly ensure a secure economic environment provides an important benchmark against which governance can be evaluated. Such an environment-which is essential for sustained growth in a market economy-can be established through a rules-based system which ensures freedom of entry into the market, access to information, and sanctity of contracts. Since creating a secure economic environment involves profound, far-reaching social change, it has historically been a complex and lengthy process in most societies. However, basing policy prescriptions on this benchmark helps avoid possible conflicts between different social and moral values.